2019
DOI: 10.4317/jced.55353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate design for in vitro mechanical testing

Abstract: BackgroundThe goal of this study was to evaluate the influence of dental substrate simulator material, and the presence of root and periodontal ligament on the stress distribution in an adhesively-cemented monolithic crown.Material and MethodsFive (5) 3D models according to the substrate simulator material and shape were modeled with CAD software for conducting non-linear finite element analysis (FEA): Tooth with and without periodontal ligament - subgroup “pl” (groups Tooth+pl and Tooth-pl), machined tooth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Although a periodontal ligament layer was not simulated, some studies have reported that this is not necessary (1,52). Other studies made representative anatomical teeth specimens lacking this dental tissue (3,26,41).…”
Section: Discussionmentioning
confidence: 99%
“…Although a periodontal ligament layer was not simulated, some studies have reported that this is not necessary (1,52). Other studies made representative anatomical teeth specimens lacking this dental tissue (3,26,41).…”
Section: Discussionmentioning
confidence: 99%
“…The cavity configuration, quality of the substrate and the type of bonding can compensate the generated stresses in this region [51]. Regarding dental pulp, according to the literature, studies that used synthetic substrates to replace human teeth in laboratory tests do not report the presence or absence of the pulp chamber space and there are also no studies that assess the influence of the pulp chamber space on compressive forces in indirect restorations [52,53]. If the resistance capacity of the cavity walls is not sufficient to com-pensate generated stresses, it may result in de-bonding at the cement-restoration and/or cement-substrate interface.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the PDL simulator is necessary in all laboratory models replicating an increase in tooth mobility when testing dental materials on traumatology or periodontology. An exception of PDL simulation can be taken into consideration when investigating mechanical properties of an experimented tooth with fiber post [38] or posterior full crowns behavior [39]. It was reported in their results that there were no significant differences in groups with and without PDL simulation.…”
Section: Discussionmentioning
confidence: 99%